Expression of stress-related genes in diapause of European corn borer (Ostrinia nubilalis Hbn.) - Popović, Željko D; Subotić, Ana; Nikolić, Tatjana V; Radojičić, Ratko; Blagojević, Duško P; Grubor-Lajšić, Gordana; Koštál, Vladimír (Comparative biochemistry and physiology. Part B, Biochemistry & molecular biology, 2015)
Diapause is a state of arrested development during which insects cope with many external and internal stressful factors. European corn borer, Ostrinia nubilalis, overwinters as a fifth instar freeze-tolerant diapausing larva. In order to explore diapause-linked stress tolerance processes, the expression of selected genes coding for stress-related proteins-glutathione S-transferase (Gst), thioredoxin (Trx), glutaredoxin (Grx), ferritin (Fer), metallothionein (Mtn), and heat shock proteins Hsp90, Hsc70, Hsp20.4, and Hsp20.1-was assessed in the fat body of diapause-destined, warm (22 °C) and cold (5 °C) acclimated diapausing larvae using the quantitative real-time PCR. Gene expression was normalised to mRNA transcripts for Actin and Rps03, and relative expression was calculated using non-diapausing larvae as a control group. During the initiation phase of diapause, the abundance of mRNA transcripts of Grx, Hsp90, Hsc70, and Hsp20.1 was significantly upregulated, Trx, Fer, Mtn, and Hsp20.1 were unchanged, while only Gst was clearly downregulated in comparison to non-diapause control. Later, in the early phase of diapause, the expression of most genes (except Trx and Hsp20.1) was upregulated in warm-acclimated larvae, while only Trx and Hsp90 were upregulated in cold-acclimated larvae. Furthermore, the relative expression of all genes (except Trx) increased gradually throughout the diapause in cold-acclimated larvae. This result indicates that the half-life of mRNAs is prolonged during diapause at low temperature, which may lead to a gradual accumulation of mRNA transcripts. Our results show that both diapause programming and temperatures affect the expression of stress-related genes in Ostrinia nubilalis.
Keywords: hmyzí proteiny; Diapause, Insect; Larva; messenger RNA; larva; zvířata; Insect Proteins; Lepidoptera; Stress, Physiological; diapauza hmyzu; fyziologický stres; Animals; exprese genu; Gene Expression; proteiny a peptidy chladového šoku; Cold Shock Proteins and Peptides; RNA, Messenger